Research of Heat Transfer Characteristics of Supercritical CO2 in Spiral Tube Heat Exchangers - Jian Cheng; Wendong Wang; Jianyang Yu; Huadong Jiang; Jianmin Gao; Dan Xu (Energies, 2024)
The spiral tube heat exchanger has the advantages of stable structure, high space utilization rate, and strong heat transfer ability. Supercritical carbon dioxide (s-CO2) has the advantages of high thermal conductivity, high specific heat capacity, and low viscosity. When the spiral tube heat exchanger uses supercritical carbon dioxide as the heat transfer medium, the two complement each other’s advantages and can further improve the heat transfer efficiency and optimize the space utilization rate. However, under the coupling influence of factors such as centrifugal force and buoyancy force, the heat transfer process of s-CO2 in the spiral tube is extremely complex. At present, there is no design criterion or empirical correlation with strong universality in the industrial field. Based on this, this paper mainly uses ANSYS FLUENT, a numerical simulation software suitable for numerical simulation, to study the influence of internal vortex field and secondary flow intensity on the thickness of thermal boundary layers through a combination of numerical simulation and theoretical analysis. At the same time, by changing various operating and structural parameters, the heat transfer characteristics of supercritical s-CO2 in the spiral tube heat exchanger are analyzed and summarized. In addition, we also established a new buoyancy factor, Fu, and tested that when Fu < 1.6 × 10−5, the effect of the buoyancy lift in the pipeline disappeared. At the same time, a correlation formula for predicting the heat transfer performance of spiral tube heat exchangers with a Nu number error less than 20% is established in this paper, which can provide solid theoretical guidance for industrial application.